Tolerance and adverse event profile with sorafenib in Indian patients with advanced hepatocellular carcinoma - Ostwal, Vikas; Gupta, Tarachand; Chopra, Supriya; Lewis, Sherly; Goel, Mahesh; Patkar, Shraddha; Shetty, Nitin; Ramaswamy, Anant (South Asian Journal of Cancer, 2017)
Background: The current standard of treatment for advanced hepatocellular cancer Hepatocellular carcinoma (HCC) is Sorafenib. Data regarding its tolerance and adverse event profile in Indian patients is scarce. Materials and Methods: The primary aim of this analysis was to assess the adverse events (Grade 3 and Grade 4 as per CTCAE v4.0) and requirements for dose reduction with sorafenib in advanced HCC. Details of consecutive patients started on 800 mg/day dosing were obtained from a prospectively maintained database (over a period of 6 months) and analyzed. Results: Thirty-nine patients were available for inclusion in the study. Median age was 58 years (range: 20–75). All patients were classified as Barcelona clinic liver cancer C. Common side effects seen were liver dysfunction (38.5%), hand-foot-syndrome-rash (HFSR) (Grade 2 and 3-25.6%), fatigue (Grade 2 and Grade 3–10.3%), and diarrhea (7.7%). Dose reduction was required in 43.6% of patients. Drug interruptions/cessation was required in 38.5% of patients within the first four months of treatment. Nearly 41% of patients required cessation of sorafenib due to intolerable side-effects while 28.2% stopped sorafenib due to progressive disease. At a median follow-up of 4.9 months, median event-free survival (EFS) was 4.20 months (95% confidence interval: 3.343–5.068). Conclusion: A higher incidence of liver dysfunction and HFSR is seen in Indian patients as compared to published data. A significant proportion of patients required cessation of sorafenib due to adverse events in our series. However, EFS remains on par with that seen in larger studies with sorafenib in advanced HCC.
Keywords: Adverse events; hepatocellular carcinoma; India; liver dysfunction; sorafenib